3(f+1)=-12

Simple and best practice solution for 3(f+1)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(f+1)=-12 equation:


Simplifying
3(f + 1) = -12

Reorder the terms:
3(1 + f) = -12
(1 * 3 + f * 3) = -12
(3 + 3f) = -12

Solving
3 + 3f = -12

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 3f = -12 + -3

Combine like terms: 3 + -3 = 0
0 + 3f = -12 + -3
3f = -12 + -3

Combine like terms: -12 + -3 = -15
3f = -15

Divide each side by '3'.
f = -5

Simplifying
f = -5

See similar equations:

| 2b-10=6 | | x*80=250 | | 10+2k=20 | | 8-3/4*0 | | -4h=-8 | | D/11=9/5 | | 22-3x-15=4x+2 | | 8-3/4*-4 | | -5/8(100) | | x(2x+5)=5 | | N-10=27 | | 5(2r-3)=r-2 | | 8-3/4*4 | | 31-17v=-14v+7 | | X+(200+X)=210 | | x-0.25=250 | | 4x+9=11x-3 | | 7x-16=4(2x-5) | | -16+12=-4(x+4) | | 3x+45y=525 | | 8-3/4x4 | | 4x-4=51 | | 8-3/44 | | (5x+2)(2x+1)=27 | | 2mn^3*-2nm^2= | | -2(x+1)=3x+8 | | y=8-3(2+3) | | 3 = c4– 1 | | 3y+12=-57 | | 3x+4yx=16 | | 6x+800=10x+1000 | | 1/2x(2x-18)=4x |

Equations solver categories